Developing Manual Book of Household Wet Waste Composting Experiment by Using Decayed Pinneapple Essence Starter for Environment/Climate Changing and Waste Recycling Topic of X Graders Madrasah Aliyah - Zerlinda Mara Ditta; Mimien Henie Irawati; Susilowati (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2017)
Waste management by composting is an alternative way that is considered most appropriate to deal with the problems of wet domestic waste. The purpose of this study was to develop a user guide for the experiment of composting wet domestic waste for the subject Environmental Change/Climate and Waste Recycling for 10th grade SMA/MA and to evaluate the effects of the use of rotten pineapple extract as the starter with the concentrations of 0%, 25%, 50 %, and 75% in the length of time of composting process. MAN 3 Malang was one of the schools in the city of Malang that had implemented Curriculum 2013, which contained the particular topic for the 10th grade. The results of the validation from materials experts, media specialists, and field experts resulted in the score of 94%, 93%, 99% respectively, and the test results from the students obtained the percentage of 91%. Based on the validation results it was concluded that the teaching materials were suitable as an alternative instructional materials in the teaching of Biology for class X IPA. The results of experimental studies indicated that the starter from the rotten pineapple extract in concentrations 75% was the most effective in speeding up the composting process.